On the art of medieval Arabic literature - Hámori, András (Princeton legacy library., 1974)
In applying the standards of modern literary criticism to medieval Arabic literature, Andras Hamori concentrates on those aspects of the literature that appear most alien to modern Western taste: the limitation of themes, the sedimentation with conventions, and the use of elusive patterns of composition. The first part of the book approaches Arabic literature from the historical point of view, concentrating on the transformations in poetic genres and poetic attitudes towards time and society in the literature between the sixth and the tenth centuries. The problems of poetic technique are the.